(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Racial relations permeate various dimensions of social life and profoundly influence cognitive development. This study is situated within a theoretical framework that questions the production and distribution of knowledge. Objective: To analyze the impacts of racial violence on cognitive development, based on the concepts of epistemicide and inventive cognition, exploring how dynamics of racial exclusion influence memory, intelligence, and learning processes. Methods: The adopted methodology was a critical reflection, grounded in the analysis of theoretical works and a review of scientific literature, which revealed an academic omission on the topic. Results: Based on the perspectives of Sueli Carneiro, Jean Piaget, Lev Vygotsky, and Virgínia Kastrup, the article identifies gaps in the Brazilian academic literature regarding the relationship between racism and cognitive development, highlighting the lack of approaches that directly connect racial dynamics to mental processes. The research points out that violent and exclusionary environments can compromise intellectual and emotional development, limiting the construction of adaptive strategies and reinforcing dynamics of social and academic exclusion. At the same time, it emphasizes the potential for cognitive resistance, where individuals and communities create new epistemologies and narratives that challenge hegemonic power structures. Conclusion: Epistemicide and scientific racism perpetuate the devaluation of racialized populations, reinforcing intellectual hierarchies and erasing alternative knowledge. In contrast, it suggests adopting educational and epistemological practices that recognize cultural plurality and inventive forms of cognition as fundamental strategies to combat racism and promote inclusive science.